Self-conception and image of context in the growth of the firm: A Penrosian History of Fiberline Composites - Ellen Mølgaard Korsager (Copenhagen Business School (CBS), 2014)
My dissertation tells a history of Fiberline Composites a small Danish producer of reinforced plastic. The purpose of telling this story, which stretches over 25 years from the company's founding in 1979 to 2004, is to discuss the process of growth. In The Theory of the Growth of the Firm economist Edith Penrose seeks to explain this process and she proposes that it is best studied through historical analysis of the individual firm. This is the case, she argues, because firm growth is a path-dependent process of accumulating and exploiting resources and because every firm exists in a specific context of time and place. The firm's available resources are exploited, or put to service, as a response to the (productive) opportunities that the firm sees and as Penrose notes the theory of the growth of firms is basically an examination of the changing productive opportunity of firms. Penrose describes productive opportunity as a subjective phenomenon. She notes that when the firm acts on such opportunities it will base its decisions on the company's own self-conception and image of context. As such these concepts are the key to explaining the growth process of the firm. The object of my dissertation is to discuss the connection between the process of firm growth and the self-conception and image of context of the firm.
hdl:10398/8999
Keywords: 650